Differential regulation of mTOR activity in retinal ganglion cells underlies their distinct susceptibility to ischemia/reperfusion - Meizhen Zhu; Yuqing Wu; Hang Gao; Fujian Qi; Xiaoyu Zhang; Yanli Ran (Communications Biology)
Abstract Retinal ischemia/reperfusion (I/R) injury drives progressive retinal ganglion cell (RGC) loss, yet mechanisms underlying neuronal type-specific vulnerability remain unclear. Using a mouse model of bilateral common carotid artery ligation, we observe decreased vessel density in the inner retina following I/R. Here, the total RGCs exhibit much more cell loss than the intrinsic photosensitive RGCs (ipRGCs). This disparity is parallel with their different mTOR activity: for ipRGCs, the mTOR activity is much higher than the total RGCs both before and after I/R. Pharmacological experiments reveal that, mTOR activation in total RGCs and high mTOR activity maintenance in ipRGCs promote rapamycin to protect the total RGCs and ipRGCs against I/R injury, respectively. Notably, the protective effects of rapamycin on total RGCs and ipRGCs manifest under different light conditions. Our findings bridge the type-specific mTOR regulation in RGCs and their distinct susceptibility to I/R injury, which offers new insights into further targeted neuroprotection.